1929
DOI: 10.1084/jem.49.6.993
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Oroya Fever

Abstract: With a view to determining the mode of infection in Carrion's disease, a study of the blood-sucking insects found in the districts of Peru where the disease prevails has been carried out, through the cooperation of The Rockefeller Institute and the Rockefeller Foundation. The material studied included ticks, mites, midges, lice, fleas, bedbugs, mosquitoes, buffalo gnats, horse-flies, "sheep ticks," 3 species of Streblidae, and 3 species of Phlebotomus, including Phlebotomus verrucarum Townsend and two new spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

1932
1932
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 7 publications
0
15
0
2
Order By: Relevance
“…Transmission of B. bacilliformis was first documented by the intradermal injection of infected, homogenized Lu. verrucarum into monkeys (Noguchi et al , 1929) and later by successful transmission by wild Lu. verrucarum induced to feed on macaques (Hertig, 1942).…”
Section: Bartonellosismentioning
confidence: 99%
“…Transmission of B. bacilliformis was first documented by the intradermal injection of infected, homogenized Lu. verrucarum into monkeys (Noguchi et al , 1929) and later by successful transmission by wild Lu. verrucarum induced to feed on macaques (Hertig, 1942).…”
Section: Bartonellosismentioning
confidence: 99%
“…Pintomyia (Pifanomyia) verrucarrum patógenos de la enfermedad de Carrión (Townsend, 1913 capturó P. verrucarum en los alrededores de la ciudad de Qui1labamba (Cusco). Es importante tener en consideración la pre sencia de P. verrucarum en esta provin cia, pues esta especie es considerada vector de la enfermedad de Carrión en el Norte y Centro de los valles occidentales y ciertos valles interandinos del Norte y Centro del Perú (Townsend, 1913;Hertig, 1942;Cáceres, 1993 (Shannon, 1929). Especie considera vector de la leishmaniosis cutánea andi «uta» en el Norte y Centro de los vall occidentales y valles interandinosdel Pe (Herrer, 1982a;Cruzado, 1987;Perez al., 1994).…”
Section: Materials Y Métodosunclassified
“…Several arthropods belonging to the orders Diptera (Noguchi et al 1929, Caceres et al, 1997, Anoplura (Ellis et al 1999), Siphonaptera (Brouqui et al 1999;Higgins et al 1996) and Parasitiformes (Schouls et al 1999, Angelakis et al 2010 have been implicated in the transmission of Bartonella spp. Previous experimental studies have demonstrated that Lutzomyia verrucarum (sandfly) are competent vectors of B. bacilliformis, which causes Carrion's disease (Breitschwerdt & Kordick 2000, Maguiña et al 2009).…”
Section: Introductionmentioning
confidence: 99%